Phenology and Growth of the Grasstree Xanthorrhoea preissii in Relation to Fire and Season - Korczynskyj, Dylan (Curtin University, 2002)
Australian grasstrees are a long-lived group of arborescent, monocotyledonous plants that persist in fire-prone landscapes. Renowned for their capacity to survive fire, and flower soon after, these species have long attracted the attention of biologists. A southwestern Australian species, Xanthorrhoea preissii, has been the subject of several recent studies, including use and verification of the "leafbase banding technique" that prompted my study. This technique, which is used to determine the age and fire history of grasstrees, correlates alternating brown- and cream-coloured, transverse bands along the stem of grasstrees with seasonal growth, and intermittent black bands with the burning of the plant. Combined, this information provides a chronology for the fire events. Fundamental to this interpretation is the assumption that grasstrees grow continually, and this growth varies annually in accordance with changes between the two contrasting seasons of its mediterranean climate. I studied X. preissii in two habitats (jarrah forest and banksia woodland) adjacent to the Perth metropolitan area, in southwestern Australia, focussing on leaf growth and phenology in relation to four factors important to the species lifecycle; climate, fire, reproduction and herbivory. Leaf production monitored for grasstrees in both habitats revealed continuous growth, oscillating between maximum rates (2.5-3.2 leaves/d) from late-spring (November) to autumn (April/May), to a minimum rate of as low as 0.5 leaf/d during winter. In additional support of the "leafbase banding technique", annual leaf production was not different from the number of leafbases comprising one cream and one brown band.Synchronised with leaf production, grasstree water potentials cycled annually, with predawn readings commonly measured as 0 MPa during winter-spring and were as low as -1.26 MPa during summer, but they never exceeded the turgor loss point (-1.85 to -2.18 MPa). The fast summer growth was characterised by a fluctuating pattern of leaf production, particularly in banksia woodland, where grasstrees reliably responded to >18 mm of rainfall. Twenty-four hours after 59 mm of simulated rainfall, grasstrees in banksia woodland showed a significant increase in water potential and increased leaf production by 7.5 times. Reflecting this result, rainfall was the best climatic variable for predicting banksia woodland grasstree leaf production rate during summer, whereas leaf production of jarrah forest grasstrees was most closely correlated with daylength. Substrate differences between the two habitats can explain this variation in leaf growth patterns. While water appears to have played an important role in the evolution of this species, growth phenology suggests that X. preissii may have retained a mesotherm growth rhythm from the subtropical early Tertiary Period. To distinguish fire-stimulated growth from the underlying growth patterns imposed by season, leaf production and starch reserves of X. preissii were compared between plants from unburnt sites and those burnt in spring and autumn. Immediately following fire, X. preissii responded with accelerated leaf production, regardless of season. Rapid leaf accumulation during the initial flush of growth was partly at the expense of starch reserves in the stem. Although this initial flush was relatively short-lived (12-32 weeks), the effect of fire on leaf production was sustained for much longer (up to 19 months).Mean maximum leaf production rate was higher for spring-burnt grasstrees (up to 6.1 leaves/d) than those burnt in autumn (up to 4.5 leaves/d), due to optimum growing conditions in late spring/early summer. Similarly, the timing of autumn burns in relation to declining temperatures with the approach of winter appeared to dictate how rapidly grasstrees resprouted. These consequences of fire season may have implications for the reproductive success of X. preissii, reflected in the greater mean spike mass of spring-burnt grasstrees (1.19 kg) than those burnt in autumn (0.78 kg). Leaf and spike growth, starch reserves and the effect of restricting light to reproductive plants on spike elongation were assessed. The emergence of the spike from within the plant's apex triggers a reduction in leaf production of up to 4.6 times that of a vegetative grasstree that is sustained until seed release 4.5-5 months later. Jarrah forest grasstrees experienced the largest trade-off in leaf production (7% lower leaf production than grasstrees in banksia woodland), and produced the shortest mature inflorescences (50% of banksia woodland grasstree inflorescences), suggesting a constraint imposed by resource availability in this habitat. During the period from inflorescence elongation to seed release starch reserves were depleted.Experimentation in the banksia woodland revealed that, although the developing spike is itself photosynthetic, it is the daily production of photosynthates by the surrounding foliage that contributes most significantly to its growth. When light was prevented from reaching the leaves the starch stored within the stem was not a sufficient substitute, evidenced by a significant reduction in spike biomass of 41%. A fire simulation experiment with a factorial design was used to assess three factors considered important for postfire grasstree leaf growth in banksia woodland: water, ash and shade. While results identified that ash and reduced shade significantly affect leaf growth, their effects were small compared with the stimulation derived solely from leaf removal by fire, simulated in this experiment by clipping. Clipping, also used to simulate herbivory, was imposed on a series of grasstrees at different frequencies. X. preissii demonstrated a strong capacity to recover in both jarrah forest and banksia woodland, even after clipping every month for 16 months. Starch reserves were depleted as the result of clipping, providing a cause of the eventual deterioration of grasstree 'health' associated with chronic herbivory. The similarity of growth responses to leaf removal independent of the mechanism (eg. fire or herbivory), provided reason to question the interpretation that grasstrees are essentially adapted to fire, rather than the alternative, that they are adapted to herbivory.